Study of the influence of modifying additives on the formation of properties of thermoplastic compositions incorporating iron oxide precipitate - LASTIVKA, Oles; ISHUTKO, Taras (Ways to Improve Construction Efficiency, 2025)
Nowadays, a wide range of approaches exists for improving the properties of PVDF-based thermoplastic coatings intended for use under intensive mechanical loads and exposure to aggressive environments. During the formation of such coatings, rheology-modifying and degassing additives play an important role, as they can influence the structural organization of the polymer matrix, minimize internal defects, reduce the likelihood of pore formation, and stabilize the film-forming process. In particular, acrylic copolymers and PTFE-modified waxes are widely used as effective modifiers; however, the mechanism of their influence on the performance characteristics of the coatings remains insufficiently explored. In this context, a systematic analysis of the potential application of functional additives in thermoplastic compositions has been carried out, which made it possible to identify the key factors affecting the development of barrier, physicomechanical, and protective properties of the material. The necessity of establishing reliable methodological approaches for studying structure formation during thermal treatment and cooling is emphasized, as these stages determine the uniformity of the coating and its long-term durability. The developed approach for assessing the influence of modifiers enables a comprehensive analysis of changes in rheological behavior, degassing processes, and final performance indicators of the coatings. The results of calculations and experimental tests demonstrate the ambiguous effect of the nature of the additives: different types of modification may either enhance or limit certain material properties. The availability of such data provides a basis for optimizing formulations and selecting the most effective systems. Thus, it has been established that the use of specialized modifiers makes it possible to purposefully regulate the processes of thermoplastic coating formation, ensuring the creation of a dense, stable structure with improved resistance to corrosion, UV radiation, and chemical exposure, which is crucial for enhancing the durability and reliability of the materials.